A Study of Some Cellulose Derivatives As Hydrogel For Control Drug Release - EI-Azmirly, M.A; Mukhlis, A.A; Khallil, B.I (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Neutral and semi-synthetic hydrophilic polymers are widely usedin pharmaceutical technology to fomlUlate as controlled release drugsdelivery systems ,cellulose derivatives is biocompatibilily, biodegradability , non-toxicity, its is a good candidate as drug carrier. In this study, polymers were used as cellulose derivatives like Methylcellulose (MC) & Soditun Carboxymetl1ylcellulose (NaCMC) as hydrogels for controlled delivery for two kinds of drugs, Cefotaxine& Amoxycill ine trihydrate i n different media (Distilled water, Normal Saline & Buffer solution  PH=2). It has been shown that for sodium Carboxymethylcellulnse the drug release rate is more than the Mcthylcellulose and that the release rate for Amoxycilli ne trihydratc is more than Cefotaxine.